Helquat dyes targeting G-quadruplexes as a new class of anti-HIV-1 inhibitors - Pávová, Marcela; Reyes-Gutiérrez, Paul Eduardo; Kozák, Jaroslav; Dobiaš, Juraj; Yurenko, Yevgen; Lepšík, Martin; Teplý, Filip; Weber, Jan (Scientific reports, 2023)
The secondary structure of nucleic acids containing quartets of guanines, termed G-quadruplexes, is known to regulate the transcription of many genes. Several G-quadruplexes can be formed in the HIV-1 long terminal repeat promoter region and their stabilization results in the inhibition of HIV-1 replication. Here, we identified helquat-based compounds as a new class of anti-HIV-1 inhibitors that inhibit HIV-1 replication at the stage of reverse transcription and provirus expression. Using Taq polymerase stop and FRET melting assays, we have demonstrated their ability to stabilize G-quadruplexes in the HIV-1 long-terminal repeat sequence. Moreover, these compounds were not binding to the general G-rich region, but rather to G-quadruplex-forming regions. Finally, docking and molecular dynamics calculations indicate that the structure of the helquat core greatly affects the binding mode to the individual G-quadruplexes. Our findings can provide useful information for the further rational design of inhibitors targeting G-quadruplexes in HIV-1.
Keywords: G-kvadruplexy; promotorové oblasti (genetika); Promoter Regions, Genetic; Terminal Repeat Sequences; HIV-1; reverzní transkripce; Reverse Transcription; G-Quadruplexes; koncové repetice